Perubahan Profil Pantai Dan Sedimen Di Teluk Bahang Dan Batu Ferringhi, Pulau Pinang - Ayob, Nor Adillah (2020)
The beach is a dynamic area and influenced by the surroundings. Any changes, pressures and activities the area will increase the rate of change of beach profile and sediment volume. Changes in physical of the beach conditions such as wind, currents, waves, elevation waves and tides and seasons change will change the shape of beach profiles, volumes and sediments that vary by month, season and place. In recent years there has been an increase in pressure from human activity and leisure that focuses on water sports, and beach recreation leading to the changes of coastal morphology, particularly the change of beach profiles, volumes and sediments and also affecting the ecosystems in that area. This study was carried out to study the process of sedimentation and sediment deposition at Teluk Bahang Beach and Batu Ferringhi Beach in the short term, analysing beach profile changes, sediment volume and size of sediment and identifying natural and human factors on beach profile changes and sediment volume. This study was conducted at Teluk Bahang Beach and Batu Ferringhi Beach, located in the northeast part of Penang, Malaysia. Data collection and sampling activities were conducted from March 2016 to February 2017 and sampling activities were conducted once a month. Sampling was carried out at eight stations, four stations are located in Teluk Bahang and four stations in Batu Ferringhi. Grains size analysis involves mean, sorting, skewness, curtosis, bulk density and porosity by using the graphic method that proposed by Folk and Ward (1957). Coastal profile and sediment volume involves measurement of coastal profile in the study area.